Development and physicochemical evaluation of flavoured nutribar using sorghum flour - SANIKA MADHAV BHOKARIKAR; MAHESHKUMAR. M; PERIYARSELVAM. S (International Journal of Pharma and Bio Sciences, 2018)
Sorghum (Sorghum bicolour) is used worldwide for different food preparations but rarely preferred in meal supplement products like energy bars. The aim of this project was to prepare a nutribar using Sorghum, naturally low gluten millet with other nutritious and unexposed ingredients. This Sorghum nutribar is prepared with major ingredients sorghum flour, organic jaggery, roasted gram, oil and other supplementary ingredients like desiccated coconut, natural flavours etc. Considering the harmful effects of artificial sweeteners, jaggery was used for the preparation as it is a rich source of iron. The proximate analysis was performed which revealed that Sorghum Nutribar provides substantial amount of carbohydrates, proteins, fats and dietary fibre. Sensory analysis was performed for three different formulations of Nutribar. The product was packed in low density polyethylene packaging material remained safe and stable during storage for 30 days .This low gluten Nutribar is organic, nutritious and multi functional with novel taste is appealing to all age groups as healthy snack or meal supplement